2014
DOI: 10.1002/job.1946
|View full text |Cite
|
Sign up to set email alerts
|

Employee judgments of and behaviors toward corporate social responsibility: A multi‐study investigation of direct, cascading, and moderating effects

Abstract: SummaryDo employee judgments of their organization's corporate social responsibility (CSR) programs relate to CSR-specific performance and in-role job performance? Can middle managers influence the formation of such judgments and what factors might moderate such cascading influences? To answer these yet unaddressed questions, we conduct three studies. Study 1 takes an organizational justice perspective and tests our baseline model. Results show that employees' CSR judgments trigger their affective commitment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 66 publications
8
163
0
1
Order By: Relevance
“…So far, research that has taken a micro-level perspective on CSR has shown that working for socially responsible companies is positively related to employees' organizational identification (Carmeli et al 2007), work engagement (Glavas and Piderit 2009), retention (Jones 2010), organizational citizenship behavior (OCB; Jones 2010; Lin et al 2010;Sully de Luque et al 2008), organizational commitment (Maignan et al 1999;Mueller et al 2012;Peterson 2004;Turker 2009b), in-role performance (Jones 2010;Vlachos et al 2014), improved employee relations (Agle et al 1999), and firm attractiveness to prospective employees (Turban and Greening 1997). Another important outcome variable, and one that is of specific interest to the present argument, is employee satisfaction.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, research that has taken a micro-level perspective on CSR has shown that working for socially responsible companies is positively related to employees' organizational identification (Carmeli et al 2007), work engagement (Glavas and Piderit 2009), retention (Jones 2010), organizational citizenship behavior (OCB; Jones 2010; Lin et al 2010;Sully de Luque et al 2008), organizational commitment (Maignan et al 1999;Mueller et al 2012;Peterson 2004;Turker 2009b), in-role performance (Jones 2010;Vlachos et al 2014), improved employee relations (Agle et al 1999), and firm attractiveness to prospective employees (Turban and Greening 1997). Another important outcome variable, and one that is of specific interest to the present argument, is employee satisfaction.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
“…For example, Bauman and Skitka (2012) argue that CSR can positively affect job satisfaction because it addresses people's need for a meaningful existence and provides them with a feeling of belonging to a larger social entity that has a positive identity. Vlachos et al (2014) likewise argued that CSR is ethically imbued and thus expresses organizational values like warmth, communion, and morality (Bauman and Skitka 2012), which in turn may foster positive employee attitudes. Rupp et al (2006) offer similar reasons as to why CSR may positively affect employee attitudes.…”
Section: The Effects Of Csr On Employee Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way an organization's CSR activities are perceived by employees seems to be significant in understanding these activities' effects at the individual level (Shin et al, 2016). A few studies have focused on determining antecedents of CSR perceptions such as the employees' perceived fit between corporate culture and the company's CSR activities and the manager's perceived in-role CSR-specific performance (Lee et al, 2013;Vlachos et al, 2014). There have been calls for ascertaining further perceived CSR antecedents (e.g., Tian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Scant research has examined employees' discretionary behaviors that target the social level or, in other words, that intend to enhance the well-being of their organization's stakeholders, including the natural environment (Crilly et al 2008;Daily et al 2009;Vlachos et al 2014). Accordingly, (Roeck & Farooq, 2017) examine societal outcome by employees' engagement in green behaviors, including employees' actions to perform work in an environmentally friendly way (e.g., recycling, rational use of resources, participation in environ-mental initiatives, setting of more sustainable policies), and societal behaviors, http://dx.doi.org/10.15405/epsbs.2018.05.63 Corresponding Author: Abdul Sami Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 774 including employees' actions that support overall community well-being even outside the work context.…”
Section: Societal Outcomementioning
confidence: 99%